Pemberdayaan Siswa dalam Menggunakan Media Sosial secara Bijak dan Bertanggung Jawab melalui Pendidikan Agama Kristen di SMAK Maryo Nekmese Hoineno - Yandry Diana Dethan; Mariyanti Adu; Fransiska Y. Nggeong; Catur Prio Purnomo; Tince D. Koroh; Christian Saetban; Frigen R. Lay (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service activity was conducted at SMAK Maryo Nekmese Hoineno, South Central Timor Regency, in response to students’ low awareness in using social media wisely and responsibly, particularly in filtering information, maintaining digital communication ethics, and utilizing social media for educational purposes. This activity aimed to equip students with digital literacy skills grounded in Christian values. The methods used were lectures and discussions. The lecture method was applied to deliver key principles of responsible social media use through Christian Religious Education, while the discussion method facilitated experience sharing, deeper understanding, and critical reflection among students. The activity involved 54 students, 8 teachers, and parent representatives. The results indicate an improvement in students’ understanding and awareness of responsible social media use. Students demonstrated better ability to verify information before sharing, maintain ethical communication, and utilize social media as a tool for learning and self-development. Additionally, the activity encouraged students to become more critical, selective, and responsible in their digital behavior. This activity highlights that integrating digital literacy with Christian Religious Education is effective in fostering students’ digital character in alignment with Christian values.